The Influence of Local Government Strategies on the Performance of Micro, Small, and Medium Enterprises (MSMEs) in North Penajam Paser Regency as a Buffer Zone for the Indonesian Capital City (IKN): A SWOT-Tows Analysis - Marbun, Makmur; Saptati, Hestrin; Saedini, Selva; Maryani, Dedeh (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Study purpose. This study aims to analyse the impact of local government strategies on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Penajam Paser Utara (PPU) Regency as a buffer zone for the Capital City of Nusantara (IKN), and to provide a comprehensive overview through strategic analysis. Materials and Methods. The study employed a mixed-method approach involving 60 MSME respondents selected through purposive sampling from a population of 152 registered MSMEs in the Alun-Alun area of PPU District. Data were collected using a Likert-scale questionnaire (1–5) and analysed using descriptive statistics and SWOT-TOWS analysis via the EFAS-IFAS system. Results. The study results indicate that the majority of respondents (96–98%) gave positive evaluations of the local government's strategies. The SWOT analysis placed SMEs in Quadrant I (Growth Strategy) with an IFAS score of 3.07 and an EFAS score of 2.83, indicating that the SO (Strength-Opportunity) strategy is a priority. Conclusion. The conclusion of this study affirms that strengthening strategies based on potential and opportunities, such as optimising the Pentas Seni and Gebyar UMKM programmes, accelerating digitalisation, and developing an integrated IKN business ecosystem, plays an important role in improving the performance of MSMEs in a sustainable manner.